Anti-inflammatory Effects of Herbal Preparations STW5 and STW5-II in Cytokine-Challenged Normal Human Colon Cells - Schneider, Mathias; Efferth, Thomas; Abdel-Aziz, Heba (Frontiers in Pharmacology, 2016)
Inflammatory bowel diseases (IBD) are chronic relapsing intestinal disorders characterized by up-regulation of pro-inflammatory cytokines followed by invasion of immune cells to the intestinal lamina propria. Standard therapies consist of anti-inflammatory or immunosuppressive drugs. Since clinical efficiency is not satisfactory and the established drugs have massive side effects, new strategies to treat IBD are required. Herein, we investigate the protective effect of the fixed combination herbal preparations STW5 and STW5-II and the contribution of the corresponding single components in an in vitro inflammation model. The normal human colon epithelial cell line, NCM460, was treated with STW5, STW5-II or their single components for 4 h followed by experimental conditions comparable to induction of colitis. A pro-inflammatory cytokine cocktail consisting of TNFα, IL-β and IFNγ was used to simulate inflammatory stimuli normally caused by immune cells. The effects on NCM460 cells were investigated by enzyme-linked immunoassay (ELISA) and Proteome Profiler®. Levels of IP-10, MCP-1, I-TAC, Groα and IL-8 were elevated in chemokine-treated cells compared to untreated cells, but significantly reduced upon pretreatment with STW5 or STW5-II. However, the single compounds revealed only little effects on protein expression. Furthermore, we investigated the effect of both combination preparations on pro-inflammatory transcription factors of the STAT family using Western blot. In addition, we tested the effects on upstream MAPK p38. Both, STW5 and STW5-II did not show any effect on MAPK p38, but were effective in reducing phosphorylated levels of STAT1. In conclusion, both combination preparations act in an anti-inflammatory manner by influencing cytokine secretion via reduced activity of the JAK/STAT1 pathway. Relevant differences between STW5 and STW5-II were not found indicating similar efficacies.